Peran Sistem Keuangan Digital (SIAPIK) dalam Mengoptimalkan Laporan Keuangan pada UMKM Pabrik Tahu Saudara Jaya - Arora Jauharotun Nabilah (Fakultas Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy; however, many MSME actors still do not apply systematic and standardized financial recording. One of the main problems faced by MSMEs is the use of simple and unstructured financial records, which makes it difficult for business owners to accurately determine profits and overall financial conditions. This study aims to examine the implementation of the Financial Information Recording Application System (SIAPIK) in optimizing the preparation of financial statements at MSME Pabrik Tahu Saudara Jaya. This research uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The object of this study is MSME Pabrik Tahu Saudara Jaya, a manufacturing-based enterprise that previously did not have adequate financial statements. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity ensured through triangulation techniques. The results indicate that prior to the implementation of SIAPIK, financial recording at MSME Pabrik Tahu Saudara Jaya was limited to recording cash inflows and outflows without clear classification between revenues and expenses. After the implementation of SIAPIK, financial recording became more structured and systematic, enabling the MSME to prepare financial statements such as the statement of financial position and the income statement in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The implementation of SIAPIK has a positive impact on improving the accuracy of financial records, facilitating financial performance monitoring, and supporting better business decision-making. Nevertheless, several technical limitations of the SIAPIK application were identified and should be considered for future development.
Reupload file repositori 09 Mei 2026_Maya FINALISASI oleh Arif 2026 Juni 15
Keywords: MSMEs; SIAPIK; Financial Statements; SAK EMKM